Oilseed radish – valuable crop of a wide range use - H. S. HERESHKO; І. S. VOLOSHCHUK; О. P. VOLOSHCHUK; V. V. HLYVA; Kh. V. BILONIZHKA (Передгірне та гірське землеробство і тваринництво)
The article highlights the national economic significance of the oilseed radish culture (Raphanus sativum d. Var. Oleifera Metrg.) іn various industries: animal husbandry, plant growing, beekeeping, medicine, cosmetics, food and technical industry. The biological characteristics of a culture rich in vitamins, macro- and microelements are described. 100 kg of green mass of oil radish contains 12–16 feed units, 12–14 % dry matter, 26–29 % crude protein, mineral compounds (sulfur, phosphorus, calcium, carotene). Post-harvest crops form up to 30 t/ha of high-protein mass, which is fed to all types of animals and poultry in mixtures with cereals – oats, corn, Sudanese grass. It is an excellent green manure for improving physical properties of the soil, reducing disease damage, which has a positive effect on the productivity of subsequent crops.